Poly(ethylene glycol) Dimethyl Ethers (PEGDME): Efficient and Recyclable Solvents for Aryne-Involved Reactions - Rai, Shweta; Samatha, Polasani; Addipilli, Ramunaidu; Mainkar, Prathama S.; Sripadi, Prabhakar; Adepu, Raju; Chandrasekhar, Srivari (Synthesis, 2022)
A variety of aryne reactions are demonstrated in poly(ethylene glycol) dimethyl ethers (PEGDMEs) as solvents without the need of any additive. The reactions proceed efficiently and good yields of the desired products are observed with PEGDME. Further, the advantage of being able to recycle PEG solvents is demonstrated in this work.
Keywords: aryne reactions; poly(ethylene glycol) dimethyl ether; metal complexes; recyclable solvent